Marketing strategy analysis of Sam Poo Kong in increasing number of visitors - Nabilah Nabilah; Michael Rudolf Bernadus (Institute of Computer Science (IOCS), 2023)
This research aimed to investigate the marketing strategies used by Sam Poo Kong, a leading tourist destination business in Semarang, to ensure the sustainability of their business. Qualitative methods were used in this study. The research utilized in-depth interviews with Sam Poo Kong's managers and CEO to collect data on their marketing approach. The findings showed that Sam Poo Kong relied heavily on two main marketing strategies, such as event promotion and social media promotion. The organization actively organizes and participates in various events to interact with potential customers, create brand awareness, and foster customer loyalty. In addition, social media promotion has also emerged as another important aspect of Sam Poo Kong's marketing strategy. By harnessing the power of social media platforms, the company effectively reaches a wider audience and engages with customers in a more interactive and dynamic way. The insights gained from this study can be useful for other businesses in the industry looking to improve their marketing strategies and maintain long-term sustainability